Fishing behaviours and fisher effect in decision‐making processes when facing depredation by marine predators. (19th June 2021) - Janc, Anaïs; Guinet, Christophe; Pinaud, David; Richard, Gaëtan; Monestiez, Pascal; Tixier, Paul
Abstract: Fishers aim to optimise cost–benefit ratios of their behaviour when exploiting resources. Avoidance of interactions with marine predators (i.e. their feeding on catches in fishing gear, known as depredation) has recently become an important component of their decisions. How fishers minimise these interactions whilst maximising fishing success is poorly understood. This issue is addressed in a sub‐Antarctic, long‐line fishery confronted with extensive depredation by sperm whales Physeter macrocephalu s and killer whales Orcinus orca by examining a 15‐year data set. Whereas a broad range of behaviours was identified from spatio‐temporal and operational descriptors, none combined high fishing success with low frequency of interactions. With experience, fishers favoured exploitation of productive patches with high frequencies of interactions over avoidance behaviours. Such decisions, although potentially optimal in the short term, are likely to intensify pressures on fish stocks and impact depredating whales. Therefore, the present study provides additional evidence to inform management decisions pertaining to the coexistence between fisheries and marine predators.